BUKAN SEKEDAR TEMPAT PINJAM BUKU: PERSFEKTIF MAHASISWA TERHADAP FUNGSI DAN KENYAMANAN PERPUSTAKAAN KAMPUS - Ratna Triani Suhendar; Ima Rahmawati; Acep Nugraha (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2026)
This study aims to explore students’ perspectives on the function and comfort of campus libraries. Using a descriptive qualitative approach, data were collected through open-ended questionnaires distributed to students from various academic backgrounds. The findings reveal that students perceive the campus library not only as a place to borrow books but also as a space for independent study, completing assignments, seeking academic references, and even taking short breaks. Aspects of comfort most appreciated by respondents include a quiet atmosphere, air conditioning, Wi-Fi access, and adequate lighting. However, some issues were also raised, such as limited book collections, a shortage of seating during peak hours, and unstable Wi-Fi connections. These findings highlight the important role of libraries in supporting students’ academic activities and the need for continued improvement in both facilities and their function as inclusive academic public spaces. Keywords: campus library, comfort, function, studentsn